Answer:
see below
Step-by-step explanation:
1.)
(0, 4)
(1, 7)
![\frac{7-4}{1-0} = 3](https://tex.z-dn.net/?f=%5Cfrac%7B7-4%7D%7B1-0%7D%20%3D%203)
y = 3x + b
(4) = 3(0) + b
b = 4
y = 3x + 4
Rate of change: 3 initial value: 4
2.)
(0, -5)
(1, -3)
![\frac{-3-(-5)}{1-0} = 2](https://tex.z-dn.net/?f=%5Cfrac%7B-3-%28-5%29%7D%7B1-0%7D%20%3D%202)
y = 2x + b
(-5) = 2(0) + b
b = -5
Rate of change: 2 initial value: -5
I dont know its right but i did
6+3*23=75
Looks like a regular hexagon
see my attachment
we put some imaginary lines and take the 2 trignles on the right and put them on teh left side
now we have a rectangle wit height 8 and width 2+4 or 6
area=8*6=48 cm^2
4a+2 because you divide 16a+8 by 4 because a square has 4 sides